Arkeologi dalam kerja pemuliharaan: Cabaran terhadap masa depan negara - Asyaari Muhamad, (Universiti Kebangsaan Malaysia, 2009)
This article discusses the role of archaeology in conservation works di Malaysia. To-date, more than 50 archeaological research projects involving conversion of a variety of heritage buidings and historical sites in the country have been carried out. Some were successful, while the others not. Following that, this article highlights the importance of archaeological research in ensuring the success of conservatrion work. Besides the point that conservation must start with the relevant archeological research, the outcome of archeaoloigcal findings need to be presered. To ensure that the originality of the heriage buildings and historical sites, the original features of the buildings and sites should be reconstructed. All these work could be done by qualify and experienced archaeologists